1999
DOI: 10.1093/humrep/14.3.787
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial pinopodes indicate a shift in the window of receptivity in IVF cycles

Abstract: The formation of endometrial pinopodes detected by scanning electron microscopy may be a specific marker for uterine receptivity. Aiming to assess the effects of ovarian stimulation on pinopode formation, we examined sequential endometrial biopsies from 17 oocyte donors. Seven normally menstruating women served as controls. Up to four samples were taken from each woman at 24-72 h intervals between days 14 and 24, giving a total of 69 samples. The day of oocyte retrieval was designated day 14 in ovarian stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
124
3
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(134 citation statements)
references
References 18 publications
4
124
3
3
Order By: Relevance
“…It is now a common practice to date endometrium according to days after the LH peak [29] [30]. Ultrastructural changes in human endometrium throughout the cycle also allow dating of the endometrium [31,32] and assist in determining the "implantation window". The implantation window is a short interval during the mid-secretory phase, when the endometrium is most receptive to blastocyst implantation.…”
Section: Endometrial Dating and The Window Of Implantationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now a common practice to date endometrium according to days after the LH peak [29] [30]. Ultrastructural changes in human endometrium throughout the cycle also allow dating of the endometrium [31,32] and assist in determining the "implantation window". The implantation window is a short interval during the mid-secretory phase, when the endometrium is most receptive to blastocyst implantation.…”
Section: Endometrial Dating and The Window Of Implantationmentioning
confidence: 99%
“…Many molecular markers such as integrins, IL-1, calcitonin, amphiregulin, EGF, HB (heparin binding)-EGF, colony stimulating factor-1, LIF, mucins, leptin, selectin-L ligands, Hoxa genes, and COX (cyclooxygenase) have been proposed to identify this period of receptivity [9,[38][39][40][41][42]. The beginning of the implantation window is also characterized by remarkable ultrastructural changes in endometrial epithelial cell morphology [31,32]. However, the implantation process is a complex and multifactorial event, with association and interplay of the different factors involved.…”
Section: Molecular and Structural Markers Of Endometrial Receptivitymentioning
confidence: 99%
“…However, this stimulation is related to supraphysiologic hormonal levels that are associated with modifications in the periimplantation endometrium [8,9], biochemical and morphologic endometrial alterations, and endometrial advancement [10,11]. Since IVF success depends not only on embryo quality, but also on endometrial receptivity and on embryo-endometrium interactions [12], these modifications might jeopardize IVF outcomes following fresh embryo transfer and not after FET [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Although cryopreservation may entail some risks to the embryo, FET may provide an endometrium with increased receptivity, as compared to that after ovarian stimulation. The timing of the Bwindow of implantation( WOI) in stimulated cycles is complicated by the fact that it may be advanced or delayed, and therefore easily mistimed [15][16][17][18][19][20][21][22]. Shapiro et al [23] showed that the clinical pregnancy rate per transfer is significantly greater in the cryopreservation group than in the fresh group in normal responders and concluded that the difference was due to impaired endometrial receptivity in fresh embryo transfer.…”
Section: Introductionmentioning
confidence: 99%